Utilization of distillers grains in feedlot cattle diets - Uwituze, Solange (Kansas State University, 2011)
Four studies evaluated effects of dry distillers grains with solubles (DDGS) containing high S concentrations on feedlot performance, ruminal fermentation, and diet digestibility by finishing cattle. Trial 1 used finishing steers fed diets based on steam-flaked corn (SFC) or dry-rolled corn (DRC), and containing 30% DDGS (DM) with 0.42% S (0.42S) or 0.65% S (0.65S). No interaction (P ≥ 0.15) between dietary S and grain processing occurred, but feeding 0.65S decreased DMI (P < 0.001) and ADG (P = 0.006) by 8.9% and 12.9%, respectively, whereas G:F was unaffected by S concentration (P = 0.25). Steers fed 0.65S had 4.3% lighter HCW (P = 0.006), lower KPH (P = 0.009), and lower yield grades (P = 0.04) than steers fed 0.42S. Concentration of H2S was inversely related (P ≤ 0.01) to ADG (r = -0.58) and DMI (r = -0.67) in cattle fed SFC, and DMI (r = -0.40) in cattle fed DRC. Trial 2 used the same treatments as in the first stud, and investigated ruminal fermentation characteristics and diet digestibility by feedlot cattle. Feeding 0.65S increased ruminal pH (P < 0.05), but decreased total VFA concentrations (P = 0.05). Steers fed 0.65S had greater ruminal NH3 concentrations (P < 0.01) than steers fed 0.42S. The magnitudes of these effects were greater in steers fed DRC than in steers fed SFC (interaction, P < 0.01). Feeding 0.65S yielded greater apparent total tract digestibilities of DM (P = 0.04) and ether extract (P = 0.03). The 3rd study evaluated effects of in vitro S titration (0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6% of DM) in substrates based on ground corn and DDGS (GC-DDGS) or ground corn with urea and soybean meal (GC-SBM). Concentrations of NH3, total VFA, IVDMD, in vitro gas production, and gas composition were unaffected by S (P > 0.05) or by the S × substrate interaction (P > 0.05). Study 4 evaluated cattle feedlot performance when exposed to DDGS containing high S levels, either continuously or intermittently. Treatments were chronic high S (CHS; 0.60% DM), chronic intermediate S (CIS; 0.50% DM), and sporadic intermediate S (SIS; oscillating from 0.40 or 0.60% S DM basis). Steers fed CHS had 11.2 and 6.1% less (P < 0.05) DMI than steers fed CIS and SIS, respectively, but there were no treatment effects on ADG, G:F, or carcass characteristics (P > 0.10). These studies suggest that changes in cattle performance and digestibility associated with high S are primarily attributable to decreased DMI, but infrequent exposure to high levels is no more harmful than continuous exposure.
Keywords: Distillers grains; Feedlot cattle; Sulfur; Animal Sciences (0475)